Phenocam - Red Green Blue (RGB) Composite Image Mean Values from Röbäcksdalen Research Area, Mast 10m Phenocam 01 - Röbäcksdalen Field Research Station (Swedish University of Agricultural Sciences, 2024)
Phenocamera RGB composite averaged daily from quality-filtered photos from 10 a.m. to 2 p.m.
Röbäcksdalen Field Research Station (2024). Phenocam - Red Green Blue (RGB) Composite Image Mean Values from Röbäcksdalen Research Area, Mast 10m Phenocam 01, 2024-01-01–2024-09-24 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/2U5VCvhV5cYrvBIUEC1SG5mL
Keywords: SITES Spectral; Calibration/Validation; Ecosystem functions; Plant Phenology; Reflectance; Vegetation Index; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap